2016
DOI: 10.4038/sljch.v45i3.8027
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices on the care of the newborn in postnatal mothers delivering at a tertiary care centre in Nepal

Abstract: Introduction: Neonatal mortality rate per thousand live births in Nepal is 24.2, and the majority of neonates die during the early neonatal period.Objective: To determine the knowledge, attitudes and practices of mothers regarding care of the newborn after delivery at a tertiary teaching hospital in Nepal. Method:A cross-sectional study employing both quantitative and qualitative study approaches was conducted in the Maternal and Child Health (MCH) unit of a tertiary hospital in East Nepal for a period of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…Evidence from different studies which was conducted in Ethiopia and other parties of world stated that mother's knowledge about neonatal danger signs were low [7][8][9][10]. Studies done in four regions of Ethiopia, Enugu state, South-East of Nigeria, Nakuru Central District, Kenya and Gondar town, North West of Ethiopia showed that mothers knowledge of three or more danger signs were 29.3%, 30.3%, 15.5% and 18.2% respectively [8,9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from different studies which was conducted in Ethiopia and other parties of world stated that mother's knowledge about neonatal danger signs were low [7][8][9][10]. Studies done in four regions of Ethiopia, Enugu state, South-East of Nigeria, Nakuru Central District, Kenya and Gondar town, North West of Ethiopia showed that mothers knowledge of three or more danger signs were 29.3%, 30.3%, 15.5% and 18.2% respectively [8,9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study conducted by Yadav et al almost 50% of mothers considered fever, vomiting and jaundice as danger signs. 10 Whereas, Aswathi et al found fever and excessive cry as to be the serious danger signs. 11 It was observed that 72 (16.7%) of the respondents had adequate knowledge in neonatal danger signs.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate knowledge and practice, while nursing the newborn decreases the risk of infections and effectively decreases morbidity and neonatal mortality. 1 Neonatal mortality of India is 30 deaths per 1000 live birth. 2 IMR of India is 41 per 1000 live birth.…”
Section: Introductionmentioning
confidence: 99%